2017
DOI: 10.3171/2017.7.peds17233
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the postoperative sagittal spinal profile in early-onset scoliosis: is there a difference between rib-based and spine-based growth-friendly instrumentation?

Abstract: OBJECTIVEAlthough the vertical expandable prosthetic titanium rib (VEPTR) and growing rod instrumentation (GRI) encourage spinal growth via regular lengthening, they can create different results because of their different fixation patterns and mechanisms in correcting scoliosis. Previous studies have focused comparisons on coronal plane deformity with minimal attention to the sagittal profile. In this retrospective study, the authors aimed to compare the evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Chen growth and coronal correction, these authors found better sagittal correction with GRs (44% vs 23%, p < 0.001). 25 Also, we do recommend rib fixation since ribs are very fragile in this condition, even if they are not dystrophic.…”
Section: Discussionmentioning
confidence: 99%
“…Chen growth and coronal correction, these authors found better sagittal correction with GRs (44% vs 23%, p < 0.001). 25 Also, we do recommend rib fixation since ribs are very fragile in this condition, even if they are not dystrophic.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and mechanism of PJK after GR treatment According to previous studies, the incidence of PJK in EOS patients after GR treatment varied from 12% to 56%, which was mainly due to different inclusion criteria and surgical strategies [10][11][12]. The incidence of PJK in our study cohort was 21.1% over an average 52.8±22.2 months of follow-up.…”
Section: Discussionmentioning
confidence: 71%
“…This is also consistent with previous research. Chen et al [10] reported that hyperkyphotic EOS (TK≥50°) tended to experience increased complications, such as rod fracture and PJK. Lee et al [25] pointed out that correction surgery would impact the overall sagittal balance of the spine and PJK might be an early-stage adjustment of the overall balance compensation by the trunk.…”
Section: General Risk Factors Of Pjkmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also consistent with previous research. Chen et al [ 10 ] reported that hyperkyphotic EOS (TK ≥ 50°) tended to experience increased complications, such as rod fracture and PJK. Lee et al [ 25 ] pointed out that correction surgery would impact the overall sagittal balance of the spine and PJK might be an early-stage adjustment of the overall balance compensation by the trunk.…”
Section: Discussionmentioning
confidence: 99%